The continuity of pre-Islamic motifs in Javanese mosque ornamentation, Indonesia - Lee-Niinioja, Hee Sook, (Archaeopress Archaeology, 2022)
This work assesses the continuity and significance of Hindu-Buddhist design motifs in Islamic mosques in Java. It investigates four pre-Islamic motifs in Javanese mosque ornamentation from the 15th century to the present day: prehistoric tumpals, Hindu-Buddhist kala-makaras, lotus buds, and scrolls.